Humor, Entertainment, and Popular Culture during World War I - Tholas-Disset, Clémentine. author. aut Link
XVI, 288 p.
Keywords: Humor and entertainment were vital to the war effort during World War I. While entertainment provided relief to soldiers in the trenches, it also built up support for the war effort on the home front. This book looks at transnational war culture by examining seemingly light-hearted discourses on the Great War.